The Factors Leading To Algerian Secondary School Teachers’ Reluctance To The Pedagogical Use Of Technology - Aycha Reffas (Al-Lisaniyyat)
Technology has become part and parcel of the teaching operation. Its effectiveness was proven by a multitude of studies investigating its usefulness in the instruction of the four language skills and other language aspects. Still, despite the increasing awareness of the urge to integrate technology; especially computer, in language instruction, there is a great deal of reluctance among teachers of the different levels to integrate it in their classrooms. This study, therefore, was an attempt to explore the set of factors leading to such reluctance and also to suggest way in order to encourage ICTs integration by instructors. According to the findings, teachers’ reluctance to technology integration stems; most of the time, from the lack of preparedness to the integration of such tools